A new problem of singular fractional differential equations. Issue 2 (2nd July 2016) - Taieb, Amele; Dahmani, Zoubir
Abstract: In this paper, we introduce a new class of nonlinear singular fractional differential equations. We axe interested in the singularity by using the contraction mapping principle and Schauder fixed point theorem. We present new results on the existence and uniqueness of solutions. Moreover, we investigate the Ulam-Hyers stability and the generalized Ulam-Hyers stability for this fractional equations. Some examples are provided to illustrate the application of our results.